Winter Peaks in Heart Failure: An Inevitable or Preventable Consequence of Seasonal Vulnerability? - Simon Stewart; Trine T Moholdt; Louise M Burrell; Karen Sliwa; Ana O Mocumbi; John JV McMurray; Ashley K Keates; John A Hawley (Cardiac Failure Review)
Climate change is a major contributor to annual winter peaks in cardiovascular events across the globe. However, given the paradoxical observation that cardiovascular seasonality is observed in relatively mild as well as cold climates, global warming may not be as positive for the syndrome of heart failure (HF) as some predict. In this article, we present our Model of Seasonal Flexibility to explain the spectrum of individual responses to climatic conditions. We have identified distinctive phenotypes of resilience and vulnerability to explain why winter peaks in HF occur. Moreover, we identify how better identification of climatic vulnerability and the use of multifaceted interventions focusing on modifiable bio-behavioural factors may improve HF outcomes.